Pengaruh Customer Satisfaction dan E-Service Quality Terhadap Customer Loyalty Pada Pengguna Lazada - Febriyanti, Karina; Mubarok, Dadan Abdul Aziz; Sofiati, Nunung Ayu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research was conducted to determine the influence of customer satisfaction and e-service quality on customer loyalty among Lazada users in Bandung Regency. This research uses a quantitative method with a verificative approach, namely using a questionnaire instrument. The data used are primary data in the form of tabulated results from questionnaire responses. The sample used by the researchers consists of Lazada users among Generation Z in Bandung Regency, aged 18 to 24 years, who have been Lazada users in the past six months, totaling 96 respondents. The determination of the sample size, the researcher used the Rao Purba formula. Based on the results of the research conducted, it shows that customer satisfaction and e-service quality simultaneously have a positive and significant impact on customer loyalty among Lazada users in Bandung Regency, which means that an increase in customer satisfaction and e-service quality together can influence the level of customer loyalty among Lazada users in Bandung Regency.